Ferroptosis: a new antidepressant pharmacological mechanism - Guangheng Zhang; Shimeng Lv; Xia Zhong; Xiangyu Li; Yunhao Yi; Yitong Lu; Wei Yan; Jiamin Li; Jing Teng (Frontiers Media S.A., 2024)
The incidence rate of depression, a mental disorder, is steadily increasing and has the potential to become a major global disability factor. Given the complex pathological mechanisms involved in depression, the use of conventional antidepressants may lead to severe complications due to their side effects. Hence, there is a critical need to explore the development of novel antidepressants. Ferroptosis, a newly recognized form of cell death, has been found to be closely linked to the onset of depression. Several studies have indicated that certain active ingredients can ameliorate depression by modulating the ferroptosis signaling pathway. Notably, traditional Chinese medicine (TCM) active ingredients and TCM prescriptions have demonstrated promising antidepressant effects in previous investigations owing to their unique advantages in antidepressant therapy. Building upon these findings, our objective was to review recent relevant research and provide new insights and directions for the development and application of innovative antidepressant strategies.